Novel Numerical Analysis of a Self-Circulating Bearing - Elizabeth J. Clifford; Christopher C. Daniels (Applied Sciences)
A novel closed-form solution representing the fluid motion within a porous bushing was created to develop a recently patented bearing configuration with a self-contained lubrication system. The configuration has a lubricant reservoir surrounding the porous bushing that continuously supplies lubricant without an external pump. In regions of low pressure, the lubricant moves into the bearing clearance; where clearance pressure is high, the lubricant is transferred to the porous bushing and refills the supply reservoir. The porous bushing’s pressure distribution was used within Darcy’s law to determine the injection velocity into the bearing clearance. Selected cases were compared with previously published work for approach validation. The validity of assuming a linear distribution within the porous media was investigated, as was the variance of the attitude angle for eccentricity and the effects of porous medium thickness and bearing parameter on bearing load capacity. It was concluded that increasing the feeding parameter increased the bearing load capacity. The porous bearing’s pressure distribution, commonly assumed to be linear, was discovered to be increasingly nonlinear near the bearing’s axial ends. The effect of nonlinearity on the bearing load capacity depended on the thickness of the porous bushing and the eccentricity of the bearing.